Exploring metabolomics to innovate management approaches for fall armyworm (Spodoptera frugiperda [J.E. Smith]) infestation in maize (Zea mays L.) - Desika, Jayasaravanan; Kalenahalli, Yogendra; Sundararajan Juliet Hepziba; Patne, Nagesh; Vivek, Bindiganavile Sampath; Ravikesavan, Rajasekaran; Nair, Sudha Krishnan; Jaba, Jagdish; Thurapmohideen Abdul Razak; Srinivasan, Subbiah; Shettigar, Nivedita (MDPI, 2024)
The Fall armyworm (FAW), Spodoptera frugiperda (J. E. Smith), is a highly destructive lepidopteran pest known for its extensive feeding on maize (Zea mays L.) and other crops, resulting in a substantial reduction in crop yields. Understanding the metabolic response of maize to FAW infestation is essential for effective pest management and crop protection. Metabolomics, a powerful analytical tool, provides insights into the dynamic changes in maize’s metabolic profile in response to FAW infestation. This review synthesizes recent advancements in metabolomics research focused on elucidating maize’s metabolic responses to FAW and other lepidopteran pests. It discusses the methodologies used in metabolomics studies and highlights significant findings related to the identification of specific metabolites involved in FAW defense mechanisms. Additionally, it explores the roles of various metabolites, including phytohormones, secondary metabolites, and signaling molecules, in mediating plant–FAW interactions. The review also examines potential applications of metabolomics data in developing innovative strategies for integrated pest management and breeding maize cultivars resistant to FAW by identifying key metabolites and associated metabolic pathways involved in plant–FAW interactions. To ensure global food security and maximize the potential of using metabolomics in enhancing maize resistance to FAW infestation, further research integrating metabolomics with other omics techniques and field studies is necessary.